Social Pedagogy in the UK: Gaining a firm foothold? - Pat Petrie (Arizona State University, 2013)
The paper asks why, unlike much of Europe, the UK has not adopted social pedagogy. It looks at the meanings of social pedagogy, including the importance of both 'social' and 'pedagogy' in understanding the term and argues that social pedagogy policy, practice and theory are interlinked and develop out of specific national contexts. There is an account of the fairly new UK interest in the subject, including some interest from government. The paper argues that this interest springs largely from concerns about the welfare of disadvantaged children, especially those that are in care, and an aspiration to improve the practice of people who work with them. There has been much less interest in social pedagogic theory. The paper concludes that unless theory, grounded in a UK context, is given equal prominence to practice, together with education and qualifications in the subject, social pedagogy will not achieve a firm footing in the UK.